The Greek wedding she never had - Shaw, Chantelle (Shaw, Chantelle. Innocent summer brides, 2021)
Twice a fiancee... finally his wife? Eleanor Buchanan broke off her engagement to Jace Zagorakis a year ago. She discovered he only wanted to marry her to gain control of her family's luxury Greek hotel - on their wedding day! Now, the devastatingly handsome tycoon is back with a second proposal. This time, innocent Eleanor must say "I do" to save the hotel from bankruptcy... knowing their chemistry has lost none of its heat. But to act on that unexplored passion as his bride, Eleanor needs to know Jace's desire for retribution doesn't outweigh his desire for her...